A Multiscale Perspective on Misfit Dislocations in Oxide Films - Sandiumenge, Felip (Frontiers in Materials, 2019)
Since misfit dislocations were first conceived by Jan H. van der Merwe in 1949 (Frank and van der Merwe, 1949), their appreciation by the scientific community has evolved from being considered a drawback to being recognized as a challenging opportunity. However, taking full advantage of all their potential sets out issues that, despite being well-established in semiconductor or metals, remain poorly understood in transition metal oxides. In this Perspective contribution we select recent findings on misfit dislocations in La0.7Sr0.3MnO3 under compressive strain to illustrate effects spanning a range of length scales like the coupling between strain and defect chemistry in and around their cores, the impact of kinetics on the morphology of dislocated films, or the subtle sensitivity of oxide properties to dislocation strain fields.